cAMP Receptor Protein Positively Regulates the Expression of Genes Involved in the Biosynthesis of Klebsiella oxytoca Tilivalline Cytotoxin - Rodríguez-Valverde, Diana; León-Montes, Nancy; Soria-Bustos, Jorge; Martínez-Cruz, Jessica; González-Ugalde, Ricardo; Rivera-Gutiérrez, Sandra; González-y-Merchand, Jorge A.; Rosales-Reyes, Roberto; García-Morales, Lázaro; Hirakawa, Hidetada; Fox, James G.; Girón, Jorge A.; et al. (Frontiers in Microbiology, 2021)
Klebsiella oxytoca is a resident of the human gut. However, toxigenic strains secrete the nonribosomal peptide tilivalline (TV), which is a pyrrolobenzodiazepine that causes antibiotic-associated hemorrhagic colitis (AAHC). The biosynthesis of TV is driven by enzymes encoded by the aroX- and NRPS-operons. In this study we determined the effect of environmental signals such as carbon sources, osmolarity, and divalent cations on the transcription of both TV biosynthetic operons. The gene expression was enhanced when bacteria was cultivated in tryptone lactose broth. Glucose, high osmolarity, and depletion of calcium and magnesium diminished gene expression, whereas glycerol increased the transcription of both TV biosynthetic operons. The cAMP receptor protein (CRP) is a major transcriptional regulator in bacteria that plays a key role in metabolic regulation. We evaluated the regulatory activity of CRP on the transcription of both TV biosynthetic operons by generating a crp isogenic mutant. The results obtained show that CRP directly activates the transcription of the genes involved in the biosynthesis of TV. Furthermore, we also demonstrated that CRP absence affected cytotoxicity of K. oxytoca on HeLa cells. Such phenotype was due to a significant reduction in TV production. This study further broaden the knowledge into the regulatory activity of CRP protein in controlling gene expression of enteropathogenic bacteria.